THE INFLUENCE OF ENVIRONMENT AND WORK MOTIVATION ON THE PERFORMANCE OF MI AL-HUSNA CILEDUG TEACHERS - Agung, Syahrum; Nufus, Tazqiyatun (prodima@fe.uika-bogor.ac.id, 2025)
Examining how factors like school climate and intrinsic motivation affect educators' productivity at Mi Al-Husna Ciledug is the primary goal of this research. Incorporating a descriptive approach into the quantitative methodology, the study utilized a saturated sample technique to recruit 61 educators for the sample. Multiple linear regression was used to evaluate the data received from the surveys. The study found that teachers' performance is positively and significantly impacted by their work environment and work motivation, and that these factors act in tandem. Schools should therefore ensure that teachers are working in an ideal setting and that they are adequately motivated to do their jobs well